How does radioisotope thermoelectric generator (RTG) work - Carla Daruich de Souza; Jong Bum Kim; Jin Joo Kim; Jin Kim; Wanook Ji; Kwang Jae Son; Sang Mu Choi; Gu Jin Kang; Jin Tae Hong (Brazilian Journal of Radiation Sciences)
Demand for energy has increasing rapidly in the last decade. In 2021 an increase in 5% was observed. Half of this demand was covered by fossil fuels, increasing CO2 emissions to record levels. With the need for new reliable steady supply sources to be used in places where maintenance is difficult, Radioisotope Thermoelectric Generators (RTG) have been given renewed attention in the past 10 years. RTGs uses radioactive decay to generate electricity. This work presents in a simple manner, the basics of RTG operation, the requirements for construction, and is followed by an example developed at KAERI. Basic Radiation Physics Concepts, RTG configuration requirements, Thermoelectric effect and materials, and calculations for electric power were presented.